Characterization and kinetic studies of oxidation desulfurization of model diesel fuel in an oscillatory baffled reactor using co-magnetic active oxides over activated carbon catalyst - Humadi, Jasim I.; Mohammed, Wadood T.; Haldhar, Rajesh (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Oxidative desulfurization (ODS) has attracted interest in the academic and industrial fields to meet new, stringent environmental legislation and produce environmentally friendly fuel.  In this work, catalytic oxidative desulfurization of dibenzothiophene (DBT) compounds in diesel fuel is studied using a co-magnetic active oxide over an activated carbon (Fe2O3 + MnO2/AC) catalyst. DBT oxidation reactions are conducted in new oscillatory and non-oscillatory baffled reactors (OBR and NOBR). New central baffles for handling catalyst particles as a fixed bed in the OBR are developed for the first time. ODS process is examined using hydrogen peroxide as oxidant under different operating parameters: temperatures: 30 - 90 °C, oxidation times: 3–12 min, frequency: 0.5 - 2 Hz, and amplitude: 3 -12 mm. The results observed that the highest desulfurization efficiency (98.1 %) is achieved under the best conditions (90 °C, 12 min, 2 Hz, and 12 mm) in OBR. The dramatic DBT oxidation in a short desulfurization time is mainly attributed to the synergistic effect of oscillatory flow and the high activity of the synthesized catalyst. The desulfurization kinetic model is examined under the best conditions. Kinetic results show that ODS reactions follow a first-order model. Also, a low activation energy (3.68 kJ/mol) is determined, which proves rapid DBT oxidation at a lower required energy.